Analisis Framing Pemberitaan Media Online Detik.Com dan Kompas.tv atas Kasus Kekerasan Seksual di Institusi KemenKop UKM RI - Restiarum, Henny; Rijnanda, Adelia Alhamdaniah; Wahyuni, Ian (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
The easy access to online news media is accompanied by the low ability of the public to understand the contents of news texts, making the public unable to grasp the true intent of a news story. News does not only provide information but also has the power to shape people's views on something. Therefore, this study aims to describe how news framing works in processing news. The method used in this research is descriptive qualitative method. The results of the study show that there are differences in framing by Detik.com and Kompas.tv media regarding cases of sexual harassment that occurred in one of the offices of state institutions, namely the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia (KemenKop UKM RI) in 2019 which returned go on. In the syntactical aspect of the Detik.com media, the statement made was a form of self-defense by the Indonesian Ministry of Cooperatives and Small and Medium Enterprises. It can be seen that the writing of the lead is a form of defense or clarification if the Indonesian Ministry of Cooperatives and Small and Medium Enterprises does not provide protection to the perpetrators and does not ignore victims of sexual harassment. Whereas on Kompas.tv the statement from the victim takes precedence. It can be seen in the leads written by Kompas.tv as a news media writing news of sexual harassment in order to tell the public the actual chronology of events from the victim's point of view and the Indonesian Ministry of Cooperatives and Small and Medium Enterprises. The thematic elements in Detik.com media are the use of explanatory coherence in the form of the word 'and' and the use of the pronouns he, we, and us. Whereas on Kompas.tv many explanatory coherences were found in the form of the word 'and' and the use of pronouns in the form of the words 'they' and 'us'. Keywords: framing analysis, sexual harassment, syntax